The nature of political philosophy : and other studies and commentaries - Schall, James V. (The Catholic University of America Press, 2022)
"A collection of essays on political philosophy, ancient philosophy, and Catholic theology, including a handful of book reviews and a short "autobiographical memoir," by a Catholic priest who taught politics at Georgetown University for decades. The book was planned and prepared by the author prior to his death but published posthumously"--